Zinc Gallogermanate Solid Solution: A Novel Photocatalyst for Efficiently Converting CO2 into Solar Fuels. (1st November 2012) - Yan, Shicheng; Wang, Jiajia; Gao, Honglin; Wang, Nanyan; Yu, He; Li, Zhaosheng; Zhou, Yong; Zou, Zhigang
Abstract As global energy demand continues to grow, the need to find a carbon‐neutral and sustainable energy source for future generations has become imperative. An especially attractive solution is to store solar energy in the form of chemical fuel via artificial photosynthesis to convert carbon dioxide into hydrocarbons. An artificial photosynthesis system is introduced based on a zinc gallogermanate solid solution photocatalyst that can convert the carbon dioxide and water into methane. The solid solution of cubic spinel ZnGa2O4 and pseudocubic inverse spinel Zn2GeO4 is successfully synthesized by hydrothermal ion exchange reaction. Introducing Zn2GeO4 into ZnGa2O4 can effectively narrow band gap by the upshift of valence band edge from the enhanced p‐d (O2p‐Zn3d) repulsion effect by incorporating s and p orbitals of Ge, and the downshift of conduction band edge by introducing the low‐energy s orbital of Ge. The zinc gallogermanate solid solution has a light‐hole effective mass, which is beneficial to improving hole mobility, and thus enhancing the ability of photocatalyst in water oxidation to provide protons for CO2 photoreduction. As a result of band gap narrowing and high hole mobility, the zinc gallogermanate solid solution exhibits high activity in converting CO2 and H2O into CH4 and O2.